Bone tissue engineering using adipose-derived stem cells and endothelial cells: Effects of the cell ratio - Mutschall, Hilkea; Winkler, Sophie; Weisbach, Volker Günter; Arkudas, Andreas; Horch, Raymund E.; Steiner, Dominik (Journal of Cellular and Molecular Medicine, 2020)
The microvascular endothelial network is essential for bone formation and regeneration. In this context, endothelial cells not only support vascularization but also influence bone physiology via cell contact-dependent mechanisms. In order to improve vascularization and osteogenesis in tissue engineering applications, several strategies have been developed. One promising approach is the coapplication of endothelial and adipose derived stem cells (ADSCs). In this study, we aimed at investigating the best ratio of human umbilical vein endothelial cells (HUVECs) and osteogenic differentiated ADSCs with regard to proliferation, apoptosis, osteogenesis and angiogenesis. For this purpose, cocultures of ADSCs and HUVECs with ratios of 25%:75%, 50%:50% and 75%:25% were performed. We were able to prove that cocultivation supports proliferation whereas apoptosis was unidirectional decreased in cocultured HUVECs mediated by a p-BAD-dependent mechanism. Moreover, coculturing ADSCs and HUVECs stimulated matrix mineralization and the activity of alkaline phosphatase (ALP). Increased gene expression of the proangiogenic markers eNOS, Flt, Ang2 and MMP3 as well as sprouting phenomena in matrigel assays proved the angiogenic potential of the coculture. In summary, coculturing ADSCs and HUVECs stimulates proliferation, cell survival, osteogenesis and angiogenesis particularly in the 50%:50% coculture.
CRIS-Team Scopus Importer:2020-05-22
Keywords: ADSC; angiogenesis; bone tissue engineering; HUVEC; osteogenesis

Comparison of Simultaneous CD34+ and CD3+ Quantification with a Modified Stem Cell Enumeration Kit on Two Different Flow Cytometers - Strobel, Joachim; Hauck-Dlimi, Barbara; Weisbach, Volker Günter; Eckstein, Reinhold; Zingsem, Jürgen; Strasser, Erwin (Clinical Laboratory, 2016)
BACKGROUND: Quantification of CD34+ cells in peripheral blood stem cell apheresis is normally performed by single platform flow cytometric measurements according to the ISHAGE protocol. Peripheral blood stem cell concentrates (PBSC) produced by apheresis normally contain many T cells. Those T cells can be used for production of donor lymphocyte infusion doses, if abundant amounts of CD34+ cells have been collected. Therefore, it is of interest to know both the CD3+ and the CD34+ cell count of allogeneic PBSC. This is the first study comparing the performance of a modified ISHAGE protocol allowing additional quantification of CD3+ cells on two different flow cytometers, the FACSCalibur and the FACSVerse, respectively. METHODS: CD45+ and CD34+ cell concentrations were measured using a standard and a modified ISHAGE protocol including CD3+ cell quantification on both machines. All cell concentrations were measured using a Trucount bead based stem cell enumeration kit. The FACSVerse machine can additionally be equipped with a sample volume sensor allowing cell quantification without using beads. The samples analysed were taken from granulocyte-colony-stimulating factor mobilized peripheral blood stem cell apheresis procedures (pre- and post-apheresis, and apheresis concentrate). RESULTS: There were no significant differences in cell concentrations measured by the standard and modified ISHAGE protocol, regardless of which machine had been used when using bead quantification. No significant differences between the results of the two flow cytometers using the modified ISHAGE protocol were observed. Pearson´s correlation was always > 0.96, and regression coefficients were higher than 0.93. The only significant differences were observed between bead quantification and volume sensor quantification on the FACSVerse machine. CONCLUSIONS: The modified ISHAGE protocol can effectively be used on both flow cytometers tested, especially if bead quantification is used.
EVALuna2:32774

ENGRAFTMENT, DIFFERENTIATION AND BIOLOGICAL EFFECTS OF CORD BLOOD-DERIVED CLONAL CELLS ADMINISTERED INTRAVENOUSLY TO NEWBORN RATS WITH HYPOXIC-ISCHEMIC BRAIN INJURY - Yang, Xiaojun; Griesmaier, E.; Wegleiter, K.; Schlager, G. W.; Weisbach, Volker Günter; Keller, M.; Park, J.; Schneider, Holm (2016)
EVALuna2:34012

Ferulic acid and human platelet lysate incorporated alginate dialdehyde-gelatin 3D (bio)printable hydrogels with biological activity - Bider, Faina; Klotschan, Artem; Kuth, Sonja; Weisbach, Volker; Boccaccini, Aldo R. (Journal of Applied Polymer Science, 2024)
This study investigates the creation of multifunctional scaffolds based on alginate dialdehyde (ADA) and gelatin (GEL) incorporating ferulic acid (FA), a phytotherapeutic agent with diverse pharmacological properties, and human platelet lysate (HPL). The multimaterial hydrogels were characterized in terms of degradation/swelling behavior showing that HPL decelerates the degradation process of ADA-GEL hydrogels in absence of FA. A FA release study confirmed that the presence of HPL does not affect the FA release ability of ADA-GEL hydrogel. A trinitrobenzenesulfonic acid (TNBS) assay confirmed no influence of HPL on the Schiff's base formation. The addition of HPL was shown to lead to a decrease in stiffness, mechanical stability, and viscosity of ADA-GEL-HPL inks. This effect was also observed for ADA-GEL-HPL inks when investigating their three-dimensional (3D) printing ability. Cytocompatibility tests and a 3D bioprinting study confirmed the beneficial impact of the addition of HPL on MC3T3-E1 cells. Moreover, an antibacterial effect provided by the addition of FA was confirmed while the incorporation of HPL led to higher VEGF-A expression by MC3T3-E1 cells. Overall, the addition of HPL and FA to ADA-GEL hydrogel results in a promising ink, which has potential for future biofabrication applications.
CRIS-Team Scopus Importer:2024-07-26
Keywords: biocompatibility; biodegradable; bioprinting; hydrogels; synthesis and processing techniques

Functional Heterogeneity of Umbilical Cord Blood Monocyte-Derived Dendritic Cells - Schweiger, Petra; Hamann, Livia; Strobel, Julian; Weisbach, Volker; Wandersee, Alexandra; Christ, Julia; Kehl, Sven; Weidenthaler, Filip; Antoniadis, Sophia; Hackstein, Holger; Cunningham, Sarah (Journal of Immunology, 2024)
Human umbilical cord blood (UCB) represents a unique resource for hematopoietic stem cell transplantation for children and patients lacking suitable donors. UCB harbors a diverse set of leukocytes such as professional APCs, including monocytes, that could act as a novel source for cellular therapies. However, the immunological properties of UCB monocytes and monocyte-derived dendritic cells (MoDCs) are not fully characterized. In this study, we characterized the phenotype and functions of UCB-MoDCs to gauge their potential for future applications. UCB exhibited higher frequencies of platelets and lymphocytes as well as lower frequencies of neutrophils in comparison with adult whole blood. Leukocyte subset evaluation revealed significantly lower frequencies of granulocytes, NK cells, and CD14+CD16− monocytes. Surface marker evaluation revealed significantly lower rates of costimulatory molecules CD80 and CD83 while chemokine receptors CCR7 and CXCR4, as well as markers for Ag presentation, were similarly expressed. UCB-MoDCs were sensitive to TLR1–9 stimulation and presented quantitative differences in the release of proinflammatory cytokines. UCB-MoDCs presented functional CCR7-, CXCR4-, and CCR5-associated migratory behavior as well as adequate receptor- and micropinocytosis-mediated Ag uptake. When cocultured with allogeneic T lymphocytes, UCB-MoDCs induced weak CD4+ T lymphocyte proliferation, CD71 expression, and release of IFN-γ and IL-2. Taken together, UCB-MoDCs present potentially advantageous properties for future medical applications.<br

Human Umbilical Vein Endothelial Cell Support Bone Formation of Adipose-Derived Stem Cell-Loaded and 3D-Printed Osteogenic Matrices in the Arteriovenous Loop Model - Winkler, Sophie; Mutschall, Hilkea; Biggemann, Jonas; Fey, Tobias; Greil, Peter; Körner, Carolin; Weisbach, Volker Günter; Meyer-Lindenberg, Andrea; Arkudas, Andreas; Horch, Raymund E.; Steiner, Dominik (Tissue Engineering - Part A, 2020)
Introduction:For the regeneration of large volume tissue defects, the interaction between angiogenesis and osteogenesis is a crucial prerequisite. The surgically induced angiogenesis by means of an arteriovenous loop (AVL), is a powerful methodology to enhance vascularization of osteogenic matrices. Moreover, the AVL increases oxygen and nutrition supply, thereby supporting cell survival as well as tissue formation. Adipose-derived stem cells (ADSCs) are interesting cell sources because of their simple isolation, expansion, and their osteogenic potential. This study targets to investigate the coimplantation of human ADSCs after osteogenic differentiation and human umbilical vein endothelial cells (HUVECs), embedded in a vascularized osteogenic matrix of hydroxyapatite (HAp) ceramic for bone tissue engineering. Materials and Methods:An osteogenic matrix consisting of HAp granules and fibrin has been vascularized by means of an AVL. Trials in experimental groups of four settings were performed. Control experiments without any cells (A) and three cell-loaded groups using HUVECs (B), ADSCs (C), as well as the combination of ADSCs and HUVECs (D) were performed. The scaffolds were implanted in a porous titanium chamber, fixed subcutaneously in the hind leg of immunodeficient Rowett Nude rats and explanted after 6 weeks. Results:In all groups, the osteogenic matrix was strongly vascularized. Moreover, remodeling processes and bone formation in the cell-containing groups with more bone in the coimplantation group were proved successful. Conclusion:Vascularization and bone formation of osteogenic matrices consisting of ADSCs and HUVECs in the rat AVL model could be demonstrated successfully for the first time. Hence, the coimplantation of differentiated ADSCs with HUVECs may therefore be considered as a promising approach for bone tissue engineering. Impact statement Due to their low donor-site morbidity, osteogenic potential and their good cell expansion, human adipose-derived stem cell is an interesting cell source. The goal of this study is to transfer thein vitroresults of increasing osteogenic potential upon cocultivation with human umbilical vein endothelial cell, to the rat arteriovenous loop model within the next step. Without using growth factors, the biomaterials, fibrin and HAp, which have already been successfully applied in clinical practice, are supposed to support bone formation by the implanted cells. The results demonstrated that vascularized bone tissue was formed in the cell-containing groups after 6 weeks.
CRIS-Team WoS Importer:2020-10-23

Identification of the novel allele, HLA-A*01:234, in the mother of a German cord blood donor - Strobel, Julian; Hauck-Dlimi, Barbara; Dullinger, Katharina; Weisbach, Volker Günter; Zingsem, Jürgen (HLA, 2018)
HLA-A*01:234 was identified by next-generation sequencing and confirmed by Sanger sequencing.
EVALuna2:213430

Identification of the novel allele, HLA-C*01:136 in a German cord blood donor originating from Azerbaijan - Zingsem, Jürgen; Hauck-Dlimi, Barbara; Dullinger, Katharina; Weisbach, Volker Günter; Strobel, Julian (HLA, 2018)
HLA-C*01:136 identified by next generation sequencing and confirmed by Sanger sequencing.
EVALuna2:213431

IGF-I and Hyaluronic Acid Mitigate the Negative Effect of Irradiation on Human Skin Keratinocytes - Sörgel, Celena; Schmid, Rafael; Stadelmann, Nina; Weisbach, Volker Günter; Distel, Luitpold; Horch, Raymund E.; Kengelbach-Weigand, Annika (Cancers, 2022)
Ionizing radiation has become an integral part of modern cancer therapy regimens. Various side effects, such as radiation dermatitis, affect patients in acute and chronic forms and decrease therapy compliance significantly. In this study, primary keratinocytes were irradiated in a 2-dimensional (2D) culture as well as on a 3-dimensional (3D) collagen-elastin matrix with doses of 2 and 5 Gy. The effect of different concentrations of IGF-I, KGF, platelet lysate (PL), high and low molecular weight hyaluronic acid (H-HA, L-HA), and adipose-derived stem cell (ADSC) conditioned medium was analyzed in respect to cell viability (WST-8), wound closure (migration), and the gene expression (quantitative real-time PCR) of 2D cultures. The 3D culture was evaluated by WST-8. A mixture of H-HA and L-HA, as well as IGF-I, could significantly stimulate the keratinocyte viability and migration which were severely reduced by irradiation. The MKI67and IL6 gene expression of irradiated keratinocytes was significantly higher after H-HA/L-HA treatment. The stimulating effects of H-HA/L-HA and IGF-I were able to be confirmed in 3D culture. A positive influence on cell viability, migration, and gene expression was achieved after the treatment with H-L-HA and IGF-I. These results open the possibility of a novel therapeutic method for both the prevention and the treatment of radiation dermatitis.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Dermatitis; Hyaluronic acid; IGF-I; Irradiation; Keratinocytes; Wound healing

Influence of Duration and Temperature of Transport and Storage Prior to Processing on Cell Quality of Cord Blood Units - A German Experience - Strobel, Joachim; Brenner, Lukas; Zimmermann, Robert; Weiss, Dominik; Zingsem, Jürgen; Eckstein, Reinhold; Weisbach, Volker Günter (Clinical Laboratory, 2015)
In Germany, cord blood needs to be transported to the processing facility to be processed and cryopreserved within 48 hours after collection according to national guidelines. During that time, a temperature of 22 ± 4 degrees C must be maintained. The purpose of this study was to analyse the influence of temperature during transport and storage prior to processing and cryopreservation on stem cells in 2460 both autologous and allogeneic umbilical cord blood samples.Total and viable CD45+ cells, total and viable CD34+ cells, and mononuclear cells (MNC) of cord blood and resulting leucocyte concentrate both before and after freezing were analysed by flow cytometry. Transport protocols and the records of temperature measuring chips used in transport were evaluated in order to analyse how long each unit was exposed to which temperature ranges.On average, the cord blood preparations were delivered within 16.4 ± 6.3 hours. No cord blood was delivered and processed later than 48 hours after donation. Temperature of transport and storage before processing had minor but sometimes significant effects on cell viability. A temperature range of 20 - 24 degrees C showed best survival rates for CD34+ cells and highest colony forming potential.The temperature prior to processing has little yet sometimes significant effects on cell viability in stem cell concentrates prepared from cord blood. However, the absolute differences in cell viabilities are quite small. Therefore, the effect is clinically negligible in a range from 4 degrees C to 28 degrees C if cryopreservation is done within 48 hours.
EVALuna2:15998

Massive intoxication with rivaroxaban, phenprocoumon, and diclofenac: A case report - Pfeiffer, Hella; Herbst, Larissa; Schwarze, Bernd; Eckstein, Reinhold; Weisbach, Volker Günter (Medicine, 2016)
RATIONALE: Oral anticoagulants and painkillers, some with an additional effect on the coagulation system, are widely used and are therefore prone to abuse and (intentional) overdose. We report the case of a patient with a massive mixed anticoagulant intoxication. PATIENT CONCERNS: The patient had ingested 1960 mg rivaroxaban, 31.5 mg phenprocoumon, 1425 mg diclofenac, and 21,000 mg metamizole in suicidal intention. DIAGNOSES: Massive mixed anticoagulant overdose. INTERVENTIONS: The patient was closely monitored. The phenprocoumon overdose was treated by the administration of vitamin K and PCC. OUTCOMES: Despite the massive inhibition of the coagulation system, the patient did not experience bleeding apart from a slight gross hematuria. LESSONS: Despite the ingestion of a massive amount of rivaroxaban, the plasma levels were not as high as feared, due to the ceiling effect of rivaroxaban absorption. Elimination occurred according to the half-life of rivaroxaban and was not unduly prolonged by the ingested quantity.
EVALuna2:32778

Measuring Lymphocyte Proliferation in Response to Specific Antigen and Mitogen Stimuli Using Flow Cytometry - Heider, Stefan; Strobel, Joachim; Mempel, Wolfgang; Eckstein, Reinhold; Weisbach, Volker Günter (Clinical Laboratory, 2016)
BACKGROUND: We present a multivariate test system using flow cytometry after in-vitro lymphocyte stimulation using 5 mitogens and 7 antigens to describe in-vitro immunofunction. METHODS: The present work is a crucial step towards establishing a simple, CFSE-based, multivariate test system that can describe the dynamics of stimulus-induced lymphocyte proliferation with considerably more precision than is possible with the radionucleotide method using 3H-thymidine. Using multicolour flow cytometry, our method allows additional phenotyping of the proliferating cells and quantifies the proliferation behaviour by precisely resolving daughter generations and determining the precursor frequency. CONCLUSIONS: Taking the calculated apoptosis parameters into account not only provides additional information about the stimulus-specific response behaviour but also improves the validity of the commonly used proliferation indices. Not only can we confirm previous findings that healthy people have marked differences in a multivariate test system in terms of the individual in-vitro reactivity to various stimuli but also substantiate that the response pattern of an individual is remarkably constant. In follow-up studies we can show for the first time that the results of immunofunctional testing do not change over a period of at least 6 months and appear to be an inherent characteristic of the individual and thus possibly have a genetic basis.
EVALuna2:32777

Monitoring of hematopoietic chimerism by real-time quantitative PCR of micro insertions/deletions in samples with low DNA quantities - Bach, Christian; Tomova, Elmira; Goldmann, Katja; Weisbach, Volker Günter; Rösler, Wolf; Mackensen, Andreas; Winkler, Jürgen; Spriewald, Bernd M. (Transfusion Medicine and Hemotherapy, 2015)
Sensitive and accurate methods to detect hematopoietic chimerism after hematopoietic stem cell transplantation (HSCT) are essential to evaluate engraftment and to monitor response to therapeutic procedures such as donor lymphocyte infusion. Continuous long-term follow up, however, requires large amounts of pre-HSCT samples limiting the application of many widely used techniques for sensitive chimerism monitoring.DNAs from 42 normal healthy donors and 16 HSCT donor/recipient pairs were employed to validate the use of allele-specific insertion/deletion (indel) quantitative real-time polymerase chain reaction (qPCR) to quantify chimerism in samples with low amounts of DNA. Consequently, indel-qPCR analyses of samples from 16 HSCT patients were compared to short-tandem repeat (STR) specific PCR analyses.Typing with reduced amounts of input DNA (15 vs. 60 ng) allowed for the reliable distinction of positive (mean threshold cycle (ct) 28.05) and negative (ct >36) signals. The high informativity of primer/probe sets, with 12 out of 19 markers exceeding 20% informativity, was confirmed in our cohort (n = 74). Importantly, a fourfold reduction of input DNA compared to published protocols did not alter PCR efficiencies and allowed for a more sensitive detection of chimerism in 7 of 16 HSCT patients compared to results obtained by STR-PCR.Our data suggest that indel-qPCR is a more sensitive technique for the detection of hematopoietic chimerism compared to STR-PCR and works efficiently for samples with low amounts of DNA.
EVALuna2:15988

Myogenic differentiation of human myoblasts and Mesenchymal stromal cells under GDF11 on NPoly-ɛ-caprolactone-collagen I-Polyethylene-nanofibers - Cai, Aijia; Schneider, Paul; Zheng, Zengming; Beier, Justus P.; Himmler, Marcus; Schubert, Dirk W.; Weisbach, Volker Günter; Horch, Raymund E.; Arkudas, Andreas (BMC Molecular and Cell Biology, 2023)
BACKGROUND: For the purpose of skeletal muscle engineering, primary myoblasts (Mb) and adipogenic mesenchymal stem cells (ADSC) can be co-cultured and myogenically differentiated. Electrospun composite nanofiber scaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability Although growth differentiation factor 11 (GDF11) has been proposed as a rejuvenating circulating factor, restoring skeletal muscle function in aging mice, some studies have also described a harming effect of GDF11. Therefore, the aim of the study was to analyze the effect of GDF11 on co-cultures of Mb and ADSC on poly-ε-caprolactone (PCL)-collagen I-polyethylene oxide (PEO)-nanofibers. RESULTS: Human Mb were co-cultured with ADSC two-dimensionally (2D) as monolayers or three-dimensionally (3D) on aligned PCL-collagen I-PEO-nanofibers. Differentiation media were either serum-free with or without GDF11, or serum containing as in a conventional differentiation medium. Cell viability was higher after conventional myogenic differentiation compared to serum-free and serum-free + GDF11 differentiation as was creatine kinase activity. Immunofluorescence staining showed myosine heavy chain expression in all groups after 28 days of differentiation without any clear evidence of more or less pronounced expression in either group. Gene expression of myosine heavy chain (MYH2) increased after serum-free + GDF11 stimulation compared to serum-free stimulation alone. CONCLUSIONS: This is the first study analyzing the effect of GDF11 on myogenic differentiation of Mb and ADSC co-cultures under serum-free conditions. The results of this study show that PCL-collagen I-PEO-nanofibers represent a suitable matrix for 3D myogenic differentiation of Mb and ADSC. In this context, GDF11 seems to promote myogenic differentiation of Mb and ADSC co-cultures compared to serum-free differentiation without any evidence of a harming effect.
CRIS-Team Scopus Importer:2023-05-26
Keywords: ADSC; Collagen; Electrospun composite nanofibers; GDF11; Myoblasts; Myogenic differentiation; Myostatin; Nanoscaffolds; poly-ε-caprolacton (PCL); Polyethylene oxide (PEO)

Oxidative stress-induced posttranslational modifications of human hemoglobin in erythrocytes - Xiang, Wei; Weisbach, Volker Günter; Sticht, Heinrich; Seebahn, Angela; Bussmann, Julia; Zimmermann, Robert; Becker, Cord-Michael (Archives of Biochemistry and Biophysics, 2013)
Posttranslational modifications (PTMs) have been reported in hemoglobin (Hb) treated with ROS/RNS in cell-free experiments. However, little is known about oxidative PTMs of Hb occurring within the erythrocytes. The aim of this study is to characterize the patterns of Hb PTMs in erythrocytes under oxidative stress. Using mass spectrometry, we investigated specifically methionine/tryptophan oxidation, tyrosine nitration, and the modification via 4-hydroxynonenal (HNE), a product of lipid-peroxidation, on Hb. We demonstrated that the treatment with H(2)O(2)/nitrite induced higher levels of Hb oxidation/nitration in purified Hb preparations than in unpurified hemolysates and erythrocytes, indicating that ROS/RNS are primarily removed by antioxidative mechanisms. We further studied Hb from erythrocytes exposed to ?-irradiation. An irradiation of 30-100 Gy triggered a remarkable increase of intracellular ROS. However, 30 Gy did not induce apparent changes in Hb oxidation/nitration and hemolysis, while Hb oxidation/nitration and hemolysis were significantly enhanced by 100 Gy, suggesting that Hb oxidation/nitration are the consequence of overwhelmed antioxidative mechanisms after oxidative attack and reflect the severity of the oxidative damage of erythrocytes. Although irradiation was known to induce lipid-peroxidation, we could not detect HNE-Hb adducts in irradiated erythrocytes. Analyzing PTM patterns suggests Hb nitration as a more suitable indicator of the oxidative damage of erythrocytes.
EVALuna2:4676

Prevention of CMV/EBV reactivation by double-specific T cells in patients after allogeneic stem cell transplantation: results from the randomized phase I/IIa MULTIVIR-01 study - Gerbitz, Armin; Gary, Regina; Aigner, Michael; Moosmann, Andreas; Kremer, Anita; Schmid, Christoph; Hirschbuehl, Klaus; Wagner, Eva; Hauptrock, Beate; Teschner, Daniel; Rösler, Wolf; Spriewald, Bernd; et al. (Frontiers in Immunology, 2023)
Introduction: Allogeneic stem cell transplantation is used to cure hematologic malignancies or deficiencies of the hematopoietic system. It is associated with severe immunodeficiency of the host early after transplant and therefore early reactivation of latent herpesviruses such as CMV and EBV within the first 100 days are frequent. Small studies and case series indicated that application of herpes virus specific T cells can control and prevent disease in this patient population. Methods: We report the results of a randomized controlled multi centre phase I/IIa study (MULTIVIR-01) using a newly developed T cell product with specificity for CMV and EBV derived from the allogeneic stem cell grafts used for transplantation. The study aimed at prevention and preemptive treatment of both viruses in patients after allogeneic stem cell transplantation targeting first infusion on day +30. Primary endpoints were acute transfusion reaction and acute-graft versus-host-disease after infusion of activated T cells. Results: Thirty-three patients were screened and 9 patients were treated with a total of 25 doses of the T cell product. We show that central manufacturing can be achieved successfully under study conditions and the product can be applied without major side effects. Overall survival, transplant related mortality, cumulative incidence of graft versus host disease and number of severe adverse events were not different between treatment and control groups. Expansion of CMV/EBV specific T cells was observed in a fraction of patients, but overall there was no difference in virus reactivation. Discussion: Our study results indicate peptide stimulated epitope specific T cells derived from stem cell grafts can be administered safely for prevention and preemptive treatment of reactivation without evidence for induction of acute graft versus host disease. Clinical trial registration: https://clinicaltrials.gov, identifier NCT02227641.
CRIS-Team Scopus Importer:2023-11-24
Keywords: allogeneic; cytomegalovirus CMV; epitope specificity; Epstein-Barr virus EBV; prevention; reactivation; stem cell transplantation (SCT)

Protein S Erlangen: a novel PROS1 gene mutation associated with quantitative protein S deficiency - Schneider, Sabine; Reissig, Julian; Weisbach, Volker Günter; Achenbach, Susanne; Hackstein, Holger; Strobel, Julian (Blood Coagulation & Fibrinolysis, 2022)
The members of a Caucasian family were genetically analyzed on suspicion of hereditary protein S deficiency. A novel mutation, c.1904T>C, associated with severe quantitative protein S deficiency was found. The novel PROS1 mutation was identified by sequencing of the PROS1 gene coding sequence. The identified c.1904T>C point mutation results in p.Phe635Ser amino acid exchange, which is located in the Laminin G-like 2 domain of protein S. Computational analysis indicates that this amino acid exchange affects the correct folding of the protein S antigen. Furthermore, this mutation is located in a region of the Laminin G-like 2 domain where changes in the amino acid sequence often result in decreased secretion. We postulate that the novel p.Phe635Ser mutation might lead to an incorrect folding, and thus, to a strongly impaired secretion of this protein S variant. We named this novel variant protein.
CRIS-Team Scopus Importer:2022-06-10

Schwann Cells Do Not Promote Myogenic Differentiation in the EPI Loop Model - Xu, Zhou; Arkudas, Andreas; Munawar, Muhammad; Schubert, Dirk W.; Fey, Tobias; Weisbach, Volker; Mengen, Lilly; Horch, Raymund E.; Cai, Aijia (Tissue Engineering - Part A, 2024)
In skeletal muscle tissue engineering, innervation and vascularization play an essential role in the establishment of functional skeletal muscle. For adequate three-dimensional assembly, biocompatible aligned nanofibers are beneficial as matrices for cell seeding. The aim of this study was to analyze the impact of Schwann cells (SC) on myoblast (Mb) and adipogenic mesenchymal stromal cell (ADSC) cocultures on poly-e-caprolactone (PCL)collagen I-nanofibers in vivo. Human Mb/ADSC cocultures, as well as Mb/ADSC/SC cocultures, were seeded onto PCL-collagen I-nanofiber scaffolds and implanted into the innervated arteriovenous loop model (EPI loop model) of immunodeficient rats for 4 weeks. Histological staining and gene expression were used to compare their capacity for vascularization, immunological response, myogenic differentiation, and innervation. After 4 weeks, both Mb/ADSC and Mb/ADSC/SC coculture systems showed similar amounts and distribution of vascularization, as well as immunological activity. Myogenic differentiation could be observed in both groups through histological staining (desmin, myosin heavy chain) and gene expression (MYOD, MYH3, ACTA1) without significant difference between groups. Expression of CHRNB and LAMB2 also implied neuromuscular junction formation. Our study suggests that the addition of SC did not significantly impact myogenesis and innervation in this model. The implanted motor nerve branch may have played a more significant role than the presence of SC.
CRIS-Team Scopus Importer:2024-02-16
Keywords: electrospun nanofibers; EPI-loop; mesenchymal stromal cells; myoblasts; myogenic differentiation; schwann cells

Schwann Cells Promote Myogenic Differentiation of Myoblasts and Adipogenic Mesenchymal Stromal Cells on Poly-ɛ-Caprolactone-Collagen I-Nanofibers - Cai, Aijia; Zheng, Zengming; Himmler, Marcus; Schubert, Dirk W.; Fuchsluger, Thomas A.; Weisbach, Volker Günter; Horch, Raymund E.; Arkudas, Andreas (Cells, 2022)
For the purpose of skeletal muscle tissue engineering, different cell types have been investigated regarding their myogenic differentiation potential, including co-cultured myoblasts and adipogenic mesenchymal stromal cells (Mb/ADSC). As neural cells enhance synaptic junction formation, the aim of this study was to co-culture Schwann cells (SCs) with Mb/ADSC on biocompatible electrospun aligned poly-ε-polycaprolacton (PCL)-collagen I-nanofibers. It was hypothesized that SCs, as part of the peripheral nervous system, promote the myogenic differentiation of Mb/ADSC co-cultures. Mb/ADSC were compared to Mb/ADSC/SC regarding their capacity for myogenic differentiation via immunofluorescent staining and gene expression of myogenic markers. Mb/ADSC/SC showed more myotubes after 28 days of differentiation (p ≤ 0.05). After 28 days of differentiation on electrospun aligned PCL-collagen I-nanofibers, gene expression of myosin heavy chains (MYH2) and myogenin (MYOG) was upregulated in Mb/ADSC/SC compared to Mb/ADSC (p ≤ 0.01 and p ≤ 0.05, respectively). Immunofluorescent staining for MHC showed highly aligned multinucleated cells as possible myotube formation in Mb/ADSC/SC. In conclusion, SCs promote myogenic differentiation of Mb/ADSC. The co-culture of primary Mb/ADSC/SC on PCL-collagen I-nanofibers serves as a physiological model for skeletal muscle tissue engineering, applicable to future clinical application
Keywords: ADSC; myoblasts; myogenic differentiation; mesenchymal stem cells; nanofibers; Schwann cells

Secretome of Adipose-Derived Stem Cells Cultured in Platelet Lysate Improves Migration and Viability of Keratinocytes - Hermann, Maike; Peddi, Ajay; Gerhards, Alexander; Schmid, Rafael; Schmitz, Deborah; Arkudas, Andreas; Weisbach, Volker Günter; Horch, Raymund E.; Kengelbach-Weigand, Annika (International Journal of Molecular Sciences, 2023)
Chronic wounds depict a silent epidemic challenging medical professionals worldwide. Regenerative medicine uses adipose-derived stem cells (ADSC) in promising new therapies. In this study, platelet lysate (PL) as a xenogen-free substitute for foetal bovine serum (FBS) in ADSC culture was used to create an ADSC secretome containing cytokines for optimal wound healing conditions. The ADSC secretome was tested on keratinocytes for migrational behaviour and viability. Therefore, human ADSC were characterized under FBS (10%) and PL (5% and 10%) substitution, regarding morphology, differentiation, viability, gene and protein expression. ADSC were then cultured in 5% PL and their secretome was used for stimulation of keratinocyte migration and viability. To enhance the effect, ADSC were treated with Epithelial Growth Factor (EGF, 100 ng/mL) and hypoxia (1% O₂). In both PL and FBS groups, ADSC expressed typical stem cell markers. PL induced a significantly higher increase in cell viability compared to FBS substitution. ADSC secretome contained various beneficial proteins which enhance the wound healing capacity of keratinocytes. This could be optimized treating ADSC with hypoxia and EGF. In conclusion, the study shows that ADSC cultivated in 5% PL can effectively support wound healing conditions and can be considered as a promising new therapy for individual treatment of chronic wound disorders.
CRIS-Team Scopus Importer:2023-03-10
Keywords: adipose-derived stem cells; cell culture; cell differentiation; molecular mechanism; personalized medicine; platelet lysate; regenerative medicine; wound healing therapy

Specific features of ex-obese patients significantly influence the functional cell properties of adipose-derived stromal cells - Schmitz, Deborah; Robering, Jan Willem; Weisbach, Volker Günter; Arkudas, Andreas; Ludolph, Ingo; Horch, Raymund E.; Boos, Anja; Kengelbach-Weigand, Annika (Journal of Cellular and Molecular Medicine, 2022)
Adipose-derived stromal cells (ADSC) are increasingly used in clinical applications due to their regenerative capabilities. However, ADSC therapies show variable results. This study analysed the effects of specific factors of ex-obese patients on ADSC functions. ADSC were harvested from abdominal tissues (N = 20) after massive weight loss. Patients were grouped according to age, sex, current and maximum body mass index (BMI), BMI difference, weight loss method, smoking and infection at the surgical site. ADSC surface markers, viability, migration, transmigration, sprouting, differentiation potential, cytokine secretion, telomere length and mtDNA copy number were analysed. All ADSC expressed CD73, CD90, CD105, while functional properties differed significantly among patients. A high BMI difference due to massive weight loss was negatively correlated with ADSC proliferation, migration and transmigration, while age, sex or weight loss method had a smaller effect. ADSC from female and younger donors and individuals after weight loss by increase of exercise and diet change had a higher activity. Telomere length, mtDNA copy number, differentiation potential and the secretome did not correlate with patient factors or cell function. Therefore, we suggest that factors such as age, sex, increase of exercise and especially weight loss should be considered for patient selection and planning of regenerative therapies.
CRIS-Team Scopus Importer:2022-07-22
Keywords: adipose-derived stromal cells; bariatric surgery; body mass index; cell function; regenerative medicine

Stammzellen aus Nabelschnurblut - ein besonderes Gut: Informationen für eine fachärztliche Beratung der Schwangeren - Goecke, Tamme W.; Jud, Sebastian; Weisbach, Volker Günter; Bender, A. W.; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2010)
CRIS-Team Scopus Importer:2020-07-01